P21 The relationship between employment status, work productivity and quality of life among patients with COPD: Cross-sectional analysis of the Birmingham COPD Cohort. (14th November 2013) - Kalirai, K; Adab, P; Jordan, R; Fitzmaurice, D; Ayres, J
Abstract : Introduction: Health related quality of life (HRQoL) tends to be lower among COPD patients, as a result of associated symptoms, comorbidities and the impact of disease on daily life. However, little is known about the association between employment status and HRQoL among COPD patients. Aims: We examined the relationships between HRQoL and employment status and occupational performance among patients with COPD. Methods: 2000 patients with COPD from primary care are being recruited into the Birmingham COPD cohort study. In addition to clinical data, employment status, work performance and HRQoL were assessed. Work performance was measured using the SPS-6 presenteeism questionnaire. HRQoL was measured using the St George's respiratory questionnaire (SGRQ-C). Interim baseline data was used to assess associations between HRQoL and employment status and HRQoL and occupational performance. Multivariate analyses were used to adjust for potential confounders. Model 1 adjusted for age, sex and smoking status. Model 2 additionally adjusted for disease severity (GOLD stage), number of co-morbidities and MRC dyspnoea score. Results: Of the 1094 patients recruited, 14.6% (n = 160) were in work. Employment status : Model 1 showed that poorer quality of life was associated with lower likelihood of being in employment (OR = 0.98, 95% CI 0.96–0.99), but the effect was not seen in model 2 (OR = 1.00, 95% CI 0.99–1.02). Work performance : increased work performance (presenteeism) was associated with a higher quality of life in both models (B coefficient 0.13, 95% CI 0.08–0.18 and 0.12, 95% CI 0.05–0.19 in models 1 and 2 respectively). Conclusions: The association between presenteeism and HRQoL has not previously been assessed in a UK COPD working population. Our findings show that after adjusting for all relevant confounders, employment status is not associated with quality of life. However, for those at work, a better quality of life is associated better work performance.